2012
DOI: 10.1186/1475-2840-11-82
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated hemoglobin (HbA1c) levels and clinical outcomes in diabetic patients following coronary artery stenting

Abstract: BackgroundDiabetes has been shown to be independent predictor of restenosis after percutaneous coronary intervention (PCI). The aim of the present study was to investigate whether a pre- and post-procedural glycaemic control in diabetic patients was related to major advance cardiovascular events (MACE) during follow up.MethodsWe evaluated 2884 consecutive patients including 2181 non-diabetic patients and 703 diabetics who underwent coronary stenting. Diabetes mellitus was defined as the fasting blood sugar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
64
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 48 publications
12
64
0
8
Order By: Relevance
“…The findings of cohort studies (18)(19)(20)(21)(22) investigating the relation between HbA 1c level and new cardiovascular events in patients with and without type 2 diabetes after cardiac interventions for coronary artery disease are in line with our findings. In these studies (18,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…The findings of cohort studies (18)(19)(20)(21)(22) investigating the relation between HbA 1c level and new cardiovascular events in patients with and without type 2 diabetes after cardiac interventions for coronary artery disease are in line with our findings. In these studies (18,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…First, hyperglycemia may induce the expression of the surface adhesion molecule P-selectin, the glycation of platelet surface proteins with a consequent membrane fl uidity decrease and a platelet adhesion increase, the activation of protein kinase C, and may exert a direct osmotic effect [9][10][11][12]. Hyperglycemia may also promote atherothrombosis via oxidation of amino groups, formation of advanced glycation end-products, endothelial dysfunction, subendothelial cellular proliferation, and increased matrix expression [12,13].…”
Section: Freedom Trial: a Brief Synopsis Of The Offi Cial Resultsmentioning
confidence: 99%
“…Other abnormalities that contribute to the enhanced platelet adhesion and activation in DM include the increased expression of the platelet receptor glycoprotein (GP) IIb/IIIa, up-regulation of platelet P2Y 12 receptor signalling, increased platelet turnover, and enhanced oxidative stress. In addition, insulin resistance may increase intracellular calcium concentration and impair the response to nitric oxide [9][10][11][12][13].…”
Section: Freedom Trial: a Brief Synopsis Of The Offi Cial Resultsmentioning
confidence: 99%
“…Therefore, patients with high follow-up HbA1c would be classified as the control group if the follow-up HbA1c level was lower than the baseline level. Kassaian et al 17 reported an association between good glycemic control (HbA1c levels ≤7.0%) and positive clinical outcomes after PCI. However, definite conclusions on the effects of glycemic control on long-term outcomes cannot be drawn because of the extremely low event rates and short follow-up duration.…”
Section: Discussionmentioning
confidence: 99%